Bacterial Spores and its Relatives as Agents of Mass Destruction - Cogliati, Sebastian Claudio (2016)
The term bioterrorism has acquired full force for the planetary consciousness from the very beginning of the new century. Indeed, from the events that occurred during October and November of 2001 with the intentional contamination with spores of pathogenic Bacillus anthracis, of letters distributed by the US public postal service and the terrorist attacks in the last months of 2015 in Egypt, France, Mali, Afghanistan, Turkey, USA and other countries have warned again about the reality of the bioterrorist threat and its immeasurable cultural and undesirable economic and political consequences. In this review we summarize the main structural characteristics that make the spores of Bacilli and Clostridia as the ideal agents for use in bioterrorism. In addition, we discuss the properties of non-sporulating Coxiella burnetii, the causative agent of Q fever, because of its peculiar resistance, high infectivity and environmental persistence that resembles true spores.